Process capability indices for profiles: a systematic literature review - Couto, Giselle Elias; Oprime, Pedro Carlos; Ganga, Gilberto Miller Devós (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose – This paper aims to provide a Systematic Literature Review on process capability indices for profile data. Design/methodology/approach – A Systematic Literature Review (SLR) was carried out, where the Web of Science, ProQuest and Scopus databases were searched, and articles from accessible academic journals, written in English and published until May 2020, were specified. Findings – The findings show that this area of research is relatively recent, with publications only found over the last decade. Furthermore, most process capability indices have been developed for simple linear profiles. Future studies may investigate more complex profiles considering the autocorrelation and non-normal condition of profile data. Originality/value – This study contributes to the academic community in the sense that it maps the available literature on process capability indices for profile data, identifies the techniques and the profile types most studied, and indicates the gaps found in the literature on the subject, providing a direction for future studies. Keywords - Process capability indices; Profiles; Functional data.